Muscle metabolism and hemodynamics of different strength endurance tests in alpine skiing - Galli, A.; Wahl, P.; Mester, J. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Strength endurance testing plays an important role in laboratory physical performance testing for alpine skiing because the tests see to be closely related to alpine skiing events in terms of intensity and duration. The aim of this study was to get a better understanding of muscle metabolism and hemodynamics during and after four different strength endurance tests.